Arthroscopic Onlay Biceps Tenodesis Utilizing 2 Knotless All-Suture Anchors - Harkirat S. Jawanda BS; Garrett R. Jackson MD; Suhas P. Dasari MD; Daniel J. Kaplan MD; Christopher M. Brusalis MD; Nikhil N. Verma MD (SAGE Publishing, 2023)
Background: Tenodesis is an effective surgical technique for the management of a pathologic long head of the biceps tendon. Tenodesis is performed with either an onlay (tendon opposed to cortical surface) or inlay (tendon docked into a reamed intra-cortical tunnel). Both techniques can be performed either from a subpectoral location, which is typically done through an open approach, or from a suprapectoral location, which is performed arthroscopically. The arthroscopic suprapectoral approach, when compared with its subpectoral counterpart, has been shown to report similar patient outcomes and complication rates. Indications: Arthroscopic suprapectoral biceps tenodesis is most commonly indicated in patients undergoing surgical treatment with anterior shoulder pain and biceps tendonitis, often associated with concomitant pathology. Less common indications include patients with superior labrum anterior and posterior tears as well as biceps tendon subluxation or dislocations. Patients with ruptured proximal biceps tendons are contraindicated, as the tendon is typically too distal for arthroscopic management. Technique Description: The biceps tendon is identified arthroscopically within the bicipital groove, just proximal to the pectoralis major tendon superior border. Suprapectoral tenodesis is then performed utilizing 2 knotless suture anchors for fixation. Results: Patient-reported outcomes following arthroscopic suprapectoral tenodesis in the literature have been found to be excellent with minimal complications. Despite current literature being inconclusive regarding the optimal site of fixation, the arthroscopic procedure minimizes the risk of infection, cosmetic deformity, and neurovascular injury that is seen in the open approach. In addition, the use of onlay fixation has traditionally avoided the risk of humeral fracture that is seen with inlay fixation. Discussion/Conclusion: This arthroscopic onlay suprapectoral tenodesis has the benefit of a time-efficient and easily reproducible technique that safely minimizes the risk of humeral fracture or neurovascular injuries. This technique historically has provided a strong fixation with excellent patient-reported outcomes. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.